The dominant view of legal ethics as an obstacle for the construction of a cultural trauma and as a cause of an individual trauma - Anzola Rodríguez, Sergio (2016)
Law and psychoanalysis are disciplines that address different questions and have different purposes. However efforts have been made to find some spaces for interdisciplinarity. One of these efforts has been to use judicial proceedings as places in which individual traumas can be transformed into cultural and social traumas. This article aims to show the risks and pitfalls of this enterprise by using a real life example. The purpose is to show how law can fail on this purpose and turn itself instead into a place for revictimization. In this latter scenario the role of lawyers and their professional duties play a key role.